2020
DOI: 10.1039/c9ew00838a
|View full text |Cite
|
Sign up to set email alerts
|

Clustering micropollutants based on initial biotransformations for improved prediction of micropollutant removal during conventional activated sludge treatment

Abstract: The lack of fundamental insights on the fate of micropollutants during activated sludge treatment presents one of the biggest challenges in optimizing their removal in wastewater treatment plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 71 publications
(67 reference statements)
1
28
2
Order By: Relevance
“…The removal efficiencies reported in Figure 1 are in line with previous studies, except for metformin, whose removal in WWTPs has been reported much higher (usually more than 80%) (Briones et al, 2016;Oosterhuis et al, 2013). Acetaminophen is known to be removed very well and carbamazepine is known for its high persistence in WWTPs all around the world (Falås et al, 2016;Joss et al, 2005;Wang et al, 2020). Metoprolol and diclofenac removal is variable in WWTPs, but their removal is often slightly higher than carbamazepine removal (Falås et al, 2016;Wang et al, 2020).…”
Section: Pharmaceutical Removal At Increasing Concentrationssupporting
confidence: 88%
See 4 more Smart Citations
“…The removal efficiencies reported in Figure 1 are in line with previous studies, except for metformin, whose removal in WWTPs has been reported much higher (usually more than 80%) (Briones et al, 2016;Oosterhuis et al, 2013). Acetaminophen is known to be removed very well and carbamazepine is known for its high persistence in WWTPs all around the world (Falås et al, 2016;Joss et al, 2005;Wang et al, 2020). Metoprolol and diclofenac removal is variable in WWTPs, but their removal is often slightly higher than carbamazepine removal (Falås et al, 2016;Wang et al, 2020).…”
Section: Pharmaceutical Removal At Increasing Concentrationssupporting
confidence: 88%
“…Fluoxetine removal was highly variable, between 25% and 70%, and the influent concentration was around 10 times lower than expected, probably due to its high sorption behaviour to several surfaces, including glass (Peake et al, 2015). For pharmaceuticals with Kd (solid-water distribution coefficient) values lower than 0.5 L/g, sorption is considered insignificant in WWTPs (Ternes et al, 2004;Wang et al, 2020). For this reason, sorption was only considered as a removal mechanism for fluoxetine and it was calculated using Equation 3.…”
Section: Pharmaceutical Removal At Increasing Concentrationsmentioning
confidence: 99%
See 3 more Smart Citations